Endoscopic and morphological characteristics of the upper gastrointestinal tract in children with food hypersensitivity - L.M. Bubyr; T.O. Kryuchko; I.M. Nesina; B.M. Filenko; T.O. Pedchenko (Zaslavsky O.Yu., 2021)
Background. In pediatric practice, increasing attention has been recently paid to the study of allergic disorders in various parts of the gastrointestinal tract, and a number of unresolved issues regarding the timely diagnosis and treatment of eosinophilic lesions of the digestive system determines the relevance of this topic. The purpose of the research was to study the endoscopic and morphological changes of the upper gastrointestinal tract in children with gastrointestinal symptoms of food hypersensitivity. Materials and methods. The study enrolled 34 children aged from 6 to 15 years with clinical signs of disorders of the upper digestive tract against the background of food hypersensitivity reactions. Depending on the level of total IgE, study participants were divided into two groups. The first group consisted of 18 children with IgE-independent allergic reactions to food (Me (Q1-Q3) 35.0 (28.0-77.5)). The second group included 16 patients with IgE-induced allergic manifestations of food hypersensitivity (Me (Q1-Q3) 240.5 (158.0-475.8)). To achieve the aim of the research, all children underwent fibroesophagogastroduodenoscopy with subsequent sampling and morphological evaluation of biopsy specimen. Results. According to the results of endoscopic examination of patients, the structure of lesions of the upper gastrointestinal tract depending on the predominance of IgE-independent or IgE-mediated gastrointestinal symptoms of food hypersensitivity did not have statistically significant differences. Morphological characteristics had some differences in the study groups and were represented by the prevalence of eosinophilic infiltration in children with IgE-induced food hypersensitivity reactions. Conclusions. The isolated gastric lesions prevailed in the endoscopic presentation of children with gastrointestinal manifestations of food allergy, and morphological signs of chronic gastritis are characterized by changes in the surface epithelium due to pronounced polymorphonuclear inflammatory infiltration in the lamina propria with a predominance of lymphocytes, neutrophils and plasma cells. The degree of activity of the eosinophilic inflammatory process was more pronounced in the group of children with IgE-induced food hypersensitivity reactions (r = 0.652; p < 0.01).